أثر القرآن الكريم في نشر اللغة العربية في الماضي والحاضر والمستقبل - Ahmed Mohamed, Ismaiel Hassanein (2011)
The Arabic language pre- revelation of the Holy Qur'an was limited in the Arabian Peninsula, it has been characterized by it beauty and graphic in the description, war and peace, and praise and slander, it was a powerful weapon used in the tribes fighting, which caused winning or losing the war, raising people and lowers others. When the light of Islam shone in the Arabian Peninsula, God chose a prophet from among the Arab, and sent down the revelation in Arabic Language, as stated in the Holy Qur’an: ( And surely thy Lord - HE is the Mighty, the Merciful. And verily this Qur'an is a revelation from the Lord of all the worlds. The Spirit, faithful to the trust, has descended with it. On thy heart, that thou mayest be a Warner. In plain and clear Arabic tongue. [al-shu’ara’: 191-195]. Several years later, Islam started to spread outside the Arabian Peninsula, as the result, many non-Arabic speakers converted to Islam, by doing so, they have to read the Qur’an. In order to read and understand the meaning, secrets, orders and prohibitions of the Holy Qur’an they have to learn Arabic language. Since then, Arabic Language is no longer confined to a particular place, ethnics or genders. In line with the above, this paper aims to investigate the impact of the Holy Qur’an in teaching/learning of Arabic language in the past, present and future, for Arabic speakers and non Arabic speakers. The paper also will investigate challenges faced by the Arabic language, especially in the era of sophisticated communication which has no limited time and/or place. The researcher will use the analytical approach to track what is written in this area; books, articles and researches to prove the impact of Holy Qur’an on teaching and learning of Arabic Language in the past, present and future.